PENGARUH SUKU BUNGA, INFLASI DAN PRODUK DOMESTIK BRUTO (PDB) TERHADAP RETURN SAHAM - Devina Amallia; Kamaluddin Rahmat; Windi Ariesti Anggraeni (Jurnal Trial Balance, 2025)
The capital market in the macroeconomic context plays a strategic role in a country's economy, particularly in raising funds and managing the optimal utilization of economic resources. Investors are required to have the ability to project future capital market conditions as a basis for making sound investment decisions. This study aims to analyze the influence of interest rates, inflation, and Gross Domestic Product (GDP) on stock returns. The population of this study includes companies listed in the IDX High Dividend 20 index on the Indonesia Stock Exchange (IDX), with a sample selected using purposive sampling, resulting in a total of 55 companies. This research employs a descriptive-verificative method with a quantitative approach. The results showed that interest rates, and inflation partially affect stock returns. GDP partially has no effect on stock returns. Interest rates, inflation and GDP simultaneously affect stock returns.